Legal capacity, developmental capacity, and impaired mental capacity in children under 16: Neurodevelopment and the law in Northern Ireland. (March 2023) - Anderson, Phil; Davidson, Gavin; Doherty, Francess; Hanna, Heather; Harper, Colin; Lynch, Gerry; McClelland, Roy; McKenna, Claire
Abstract: When people of any age, despite all possible support being provided, are unable to make a necessary decision, then it is important to have a legal framework which promotes and protects their rights. There is ongoing debate about how this can be achieved, in a non-discriminatory way, for adults but it is also an important consideration for children and young people. In Northern Ireland, the Mental Capacity Act (Northern Ireland) 2016, when fully implemented will provide a non-discriminatory framework for those aged 16 and over. Arguably this addresses discrimination based on disability but continues to discriminate based on age. This article explores some of the possible ways the rights of those aged under 16 could be further promoted and protected. These approaches may include: retaining the current combination of statute law but developing new guidance to inform practice for those aged under 16; codifying Gillick to clarify under what circumstances those aged under 16 can accept, and possibly also refuse, interventions; amend the Children (Northern Ireland) Order 1995 to provide a more comprehensive framework for health and welfare decision making; amend and extend the Mental Capacity Act (Northern Ireland) 2016 to apply to those aged under 16; or develop a new law specifically focused on the emerging capacity of those aged under 16. There are complex issues involved including how to consider emerging or developmental decision-making ability, and the role of those with parental responsibility, but the complexities involved should not prevent these issues being addressed. Highlights: A legal framework is needed for when people are unable to make decisions. Compulsory intervention based only on mental disorder and risk criteria is discriminatory. A non-discriminatory approach could be a framework based on the relevant decision-making ability. In Northern Ireland this approach is being developed for everyone aged 16 and over. Extending this approach to those under 16 must consider complex issues including emerging capacity.